Oral Manifestations of Crohn's Disease: A Case Report and Review of the Literature - Victoria L. Woo (Hindawi Limited, 2015)
Crohn's disease (CD) is an inflammatory disorder of the gastrointestinal tract that is likely caused by an inappropriate mucosal inflammatory response to intestinal bacteria in a genetically predisposed host. The lesions of CD can involve any region of the GI tract as well as extraintestinal sites such as the skin, joints, and eyes. The most common presenting symptoms are abdominal pain and prolonged diarrhea associated with fevers, fatigue, and malaise. Delayed growth and failure to thrive may also be observed in pediatric patients. Oral manifestations of CD are known as oral CD and may precede GI involvement, thus serving as early markers of this condition. We describe a 6-year-old male who presented with oral lesions as his initial manifestation of disease and review the current literature pertaining to oral CD.